Vivência do sofrimento moral na estratégia de saúde da família: visão dos profissionais - Cecília Maria Lima Cardoso (2015)
The Family Health Strategy (FHS) implantation aims to produce an effort directed to the change in prevalent care and management models, suggesting new arrangements in the work process of the teams and in the relationship with the users of the Unified Health System (UHS). In the context of the FHS, health teams are organizing the local demand, planning health actions, and, mainly, are agents of social transformation. Such scenario of changes in the health care paradigm can trigger the professional experience of the ethical problems and moral distress (MD), understood as pain or distress that affects the mind, body or interpersonal relationships at work, when a person makes a moral judgment about what is right to do, but is prevented from doing it by restrictions of various orders. Therefore, the aim of this study was to understand the experience of MD in the daily professionals FHS. This is a case study with a qualitative approach, conducted with 28 professionals of family health teams in the municipality of Paraopeba, Minas Gerais, including doctors, nurses, nursing technicians and community health agents. After the research approval by the Ethics Committee of UFMG (nº749142) and the signature of the Informed Consent Term by the subjects, we proceeded to the collection of data through interviews using semi-structured questionnaire, participant observation and projective technique. The data were analyzed according to Bardin´s Content Analysis. In the analysis, five categories emerged despite the experience of MD in the FHS: "Understanding the FHS by the view of those who execute it: inconsistencies between discourse and practice," in which critical reflection on the work of professionals working in the FHS was highlighted, since a distance between the discourse of professional performance in the FHS and the ways of acting in practice was perceived as routine services, with indications of generating ethical problems and MD; "Health Services Organization and Working Conditions in the FHS as MD generators", in this category, the issues related to the services organization involving structural conditions of the units; shortage of material inputs, improvisation, work overload, lack of professional appreciation and weaknesses of Healthcare Networks, appear as disregard to the compliance of SUS principles and denote ethical implications to professionals, becoming a prominent source of impotence feelings, frustration and discouragement at work; in " Professional Assignments and Interpersonal Relationships at Work in the FHS as MD generators" it was possible to evidence a fine line between the definition of the roles of each team member and the execution of the tasks, which may lead to professional conflicts inherent in professional practice issues. In interpersonal relationships, there were factors related to medical hegemony and little participative management, causing conflicts in relationships prone to ethical problems and MD; in the category "MD Experience in FHS: The Reality Expressed by Daily Scenes", narratives of real events of daily work unveiling the MD in the FHS; and, finally, "Strategies for Facing MD: An Agenda for Preserving Professional Values", identifies key strategies adopted by professionals to face the MD in order to avoid the naturalization of this phenomenon in health practices. These results indicate the presence of ethical problems and MD in the FHS as routine situations in service, and, once not depicted, in most of the times, in classical dilemmas and dramatic issues, become invisible, and less discussed in services. Therefore, it is necessary to reflect on the experience of the MD at work, focusing on the conditions and elements involved that cause suffering to promote awareness of moral and ethical issues, promoting the role and the transformation of the subjects.